Statystyczna analiza struktury kapitału w spółkach giełdowych w latach 2000-2005 - Łuniewska, Małgorzata; Tarczyński, Waldemar (A Statistical Analysis of Capital Structure in Listed Companies Between 2000 and 2005, 2007)
In the process of investing on the capital market, one of the crucial elements of the process is the evaluation of the economic/financial condition of the company. This evaluation is often the result of a ratio analysis, which involves the examination of liquidity, profitability, company debt, management efficiency and market indicators. The most frequently accepted factor in analyses is general debt ratio, which is an evaluation of the capital structure. The capital structure is one of the factors which influences the company's current economic performance, as well as the profitability of the company's development ventures. A statistical analysis of capital structure was carried out in the article and efforts were undertaken to answer the questions whether it is possible to observe regularities in this domain and what the influence of the capital structure on the economic/financial condition of the company is. The research was conducted on selected listed companies with the highest liquidity and capitalization, excluding banks (these were stock companies included in the WIG20 index in the first quarter of 2005). Quarterly data from the first quarter of 2000 to the last quarter of 2005 was analyzed during the research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 343-354